Effects of Anastomotic Posterior Urethroplasty (Simple or Complex) on Erectile Function: a Prospective Study - Hosseini, Jalil; Soleimanzadeh Ardebili, Farzen; Fadavi, Behrouz; Haghighatkhah, Hamidreza (Urology Journal, 2018)
Purpose: Although improvements in urological function have been less challenged, concern about andrological problems following urethral stricture surgeries has been growing in recent years. The aim of this study is to evaluate the role of the anastomotic urethroplasty itself on erectile function in patients with posterior urethral injuries. Materials and Methods: In this prospective cohort study, patients with urethral strictures referring to Tajrish Hospital during October 2013 to August 2016 for anastomotic urethroplasty, were included. All subjects underwent radiologic studies along with rigid and flexible cystoscopy before surgery. Erectile function was evaluated before surgery (twice, addressing pre-traumatic and pre-operational conditions) and after surgery (3 and 6 months post-operatively) via IIEF-5 erectile function questionnaire and color Doppler ultrasound assessment of penile vasculature. Results: A total of 65 patients with an average age of 30.6 ± 6.1 years were included. A significant decline was observed in erectile function of patients after the injury based on IIEF-5 questionnaire filled twice separately addressing patient conditions before and after trauma (mean IIEF score 23.15 ± 0.93 to 13.45 ± 5.43, P = .001). There was also a significant difference in erectile function of subjects with pelvic fractures compared to those without pelvic fractures (10.43 ± 3.78 vs. 18.96 ± 3.18 P = .001). Univariate and multivariate analyses showed that urethroplasty itself does not significantly affect erectile function in patients according to penile color Doppler ultrasonography (peak cystolic velocity at cavernosal arteries before and after surgery: right 26.87 ± 6.93 vs26.16 ± 6.53 respectively and left 27.23 ± 5.21 vs 26.52 ± 4.38 respectively) and IIEF-5 erectile function questionnaire (13.12 ± 5.38 vs. 13.54 ± 5.44; P = .26). Conclusion: The results of this study showed that urethroplasty does not significantly affect erectile function in patients with urethral strictures. The marginal results showing a negatively affected erectile function in patients with complex strictures may be attributed to a real impact of the surgery in this subgroup or lower number of these cases in our study.